Knowledge of, attitudes toward and practices of ethics of war of the officers and soldiers of the Zambia Army - William Sikazwe; Evance Kalula; Eustarckio Kazonga (Scientia Militaria, 2022)
Since the end of the world wars, the demise of the Cold War and the end of liberation wars in Africa, the changing character of warfare has given birth to uncertainties about how states will respond to acts of aggression in the face of ethics of war, or the moral rules of war. It has become difficult for states to conduct permissible self-defence and other-defence against non-state actors or sub-state groups, which do not have a sovereign (political and territorial integrity) to protect. In the face of this reality, it is not known how much knowledge military personnel world over have on ethics of war, what their attitude towards ethics of war is, and how they practice these ethics of war during war and operations other than war. Research was therefore conducted to assess knowledge of, attitudes toward and practices of the ethics of war of officers and soldiers of the Zambia Army.